Pemanfaatan Koleksi Umum oleh Pemustaka di Kantor Perpustakaan, Arsip, dan Dokumentasi Kabupaten Pesisir Selatan - Hazmi, Ricie Hijrahtul; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the use of public collections by the visitors in the Office of Libraries, Archives, and Documentation South Coastal District. Data were collected through direct observation and interviews with librarians who are willing to respond. Analyzing data descriptively and with a literature study related to the discussion in the research. Based on analyzing the data, it can be concluded that the use of the general collection by the visitors in the Office of Libraries, Archives, and Documentation South Coastal District has not been evenly distributed. General collection of the most frequently used is the type collection of the novel (800). In the utilization of the visitors can find a collection of collections needed to support catalog card catalog card yet available in the Office of Libraries, Archives, and Documentation South Coastal District is not in accordance with the collection available on the shelves. This resulted in the visitors have to find a collection one by one on the shelves and will spend a lot of time user library. Keywords: utilization; general collection; the visitors; Â the library